ESTIMASI PELAYANAN OPERASIONAL BUS LANE DI BANDUNG - Kusuma, Gatot Perdana; Sutandi, A. Caroline; Santosa, Wimpy; Joewono, Tri Basuki (Jurnal Transportasi, 2007)
AbstractÂ As a way to improve the service of public transportation, there is a plan to operate bus lane in the city of Bandung with Cibeureum-Cibiru as a selected route. The aim of this study is to estimate the number of passenger and also the operational characteristics of bus lane for 20 years, i.e. from 2007 up to 2027. By employing deterministic approach, several operational characteristics, i.e. frequency, headway, and number of bus, are estimated. Two types of bus are employed, i.e. medium and regular bus with 55 and 85 passengers. Number of passengers for the year of 2007 and 2027 are 1,562 and 2,321 passengers per hour per direction, respectively. In 2007, frequency for medium and regular bus is 14 and 10 bus per hour, while the headway is 4.3 and 6 minutes. Number of medium and regular bus for the year of 2007 is 27 and 20 units.Keywords: bus lane, pelayanan operasional, estimasi, angkutan umum.